Effects of particle size on the quality attributes of reconstituted whole-wheat flour and tortillas made from it. (September 2016) - Liu, Ting; Hou, Gary G.; Lee, Bon; Marquart, Len; Dubat, Arnaud
Abstract: The objective of this study was to examine the effects of whole-wheat flour (WWF) particle size on the quality attributes of WWF tortillas. WWF samples of different particle size distributions from commercial U.S. hard white (median diameters: 175.7, 128.6, 120.0, 108.5 and 102.4 μm), hard red winter (median diameters: 173.7, 133.6, 124.3, 110.8 and 104.2 μm) and hard red spring (median diameters: 173.7, 132.1, 124.7, 112.9, 106.3 μm) wheat classes were obtained by fine grinding of bran and shorts and re-combining with the rest of fractions. For all three wheat classes, as WWF median particle size decreased, the L* (lightness) value decreased but the adjusted damaged starch, polyphenol oxidase activity, and a* and b* values increased. Mixolab data showed that development time decreased as WWF particle size was reduced, while stability time and starch retrogradation increased. As for WWF tortilla quality, the breaking force and extensibility increased with decreasing particle size from ∼175 to 129–134 μm, but diameter and thickness were not significantly affected. The results indicated that reducing the median particle sizes of WWFs from ∼175 μm to ∼130 μm would significantly improve the WWF tortilla quality. Highlights: Finer particle size WWF had darker color and more adjusted damaged starch. Reducing WWF particle size decreased water absorption and dough development time. Finer WWF particle size increased dough stability time and starch retrogradation. Reduction of WWF particle size increased tortilla breaking force and extensibility. Fine grinding of WWF from 175 to 130 μm improved tortilla baking performance.